Compliance with Prescription Guidelines for Glucose-Lowering Therapies According to Renal Function: Real-Life Study in Inpatients of Internal Medicine, Endocrinology and Cardiology Units - Lohan, Laura; Galtier, Florence; Manson, Thibault; Mura, Thibault; Castet-Nicolas, Audrey; Faure, Delinger; Chapet, Nicolas; Leclercq, Florence; Pasquié, Jean Luc; Roubille, François; Roubille, Camille; Blain, Hubert; et al. (Medicina (Kaunas, Lithuania), 2021)
Background and objectives: Renal failure is a contraindication for some glucose-lowering drugs and requires dosage adjustment for others, particularly biguanides, sulfonylureas, and inhibitors of dipeptidyl peptidase 4. In this study, we assessed adherence to prescription recommendations for glucose-lowering drugs according to renal function in hospitalized diabetic subjects. Materials and Methods: This prospective cohort study was carried out over a 2-year period in a university hospital. Glomerular filtration rate (GFR) was determined by averaging all measurements performed during hospitalization. Glucose-lowering drug dosages were analyzed according to the recommendations of the relevant medical societies. Results: In total, 2071 diabetic patients (53% hospitalized in cardiology units) were examined. GFR was <30 mL/min/1.73 m2 in 13.4% of these patients, 30–44 in 15.1%, 45–60 in 18.3%, and >60 in 53.3%. Inappropriate oral glucose-lowering treatments were administered to 273 (13.2%) patients, including 53 (2.6%) with a contraindication. In cardiology units, 53.1% and 14.3% of patients had GFRs of <60 and <30 mL/min/1.73 m2, respectively, and 179 (15.4%) patients had a contraindication or were prescribed an excessive dose of glucose-lowering drugs. Conclusions: We showed that the burden of inappropriate prescriptions is high in diabetic patients. Given the high number of patients receiving these medications, particularly in cardiology units, a search for potential adverse effects related to these drugs should be performed.